Đặt x = 4 - m; y = 4 + m
=> x2 + y2 = (4 - m)2 + (4 + m)2 = 16 - 8m + m2 + 16 + 8m + m2 = 32 + 2m2
Vì m2 >= 0 => 2m2 >= 0
=> 32 + 2m2 >= 32
Dấu bằng xảy ra khi: m2 = 0 => m = 0
Vậy x2 + y2min = 32 <=> x = y = 4
Ta có: \(x+y=4\) \(\Rightarrow\) \(y=4-x\)
Do đó: \(A=x^2+y^2=x^2+\left(4-x\right)^2=x^2+16-8x+x^2=2x^2-8x+16=2\left(x^2-4x+4\right)+8\)
\(A=2\left(x-2\right)^2+8\ge8\) với mọi \(x;y\)
Dấu \("="\) xảy ra \(\Leftrightarrow\) \(\left(x-2\right)^2=0\)
\(\Leftrightarrow\) \(x-2=0\)
\(\Leftrightarrow\) \(x=2\)
\(\Rightarrow\) \(y=2\) (do \(x+y=4\) )
Vậy, \(Min\) \(A=8\) \(\Leftrightarrow\) \(x=y=2\)